PENYULUHAN PEMBUANGAN LIMBAH PADA MASYARAKAT LINGKUNGAN III DAN IV KELURAHAN WINANGUN SATU KECAMATAN MALALAYANG, KOTA MANADO: Counseling On Waste Disposal In Environmental Communities III And IV Winangun Satu Village, Malalayang District, Manado City - Sri Seprianto Maddusa; Afnal Asrifuddin; Resika; Liliany Tatambihe; Abril Loisa Isabel Wowor; Lisnawati Valencia; Chikita Amanda Ibur; Brian Septian Palembo (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
This community service aims to provide knowledge and understanding to the community of Environment III and IV of Winangun Satu Village, Malalayang District regarding the dangers of disposing of waste (bathing/washing) into sewers and things that can be done to prevent the impact that this waste can have. The method used in this counseling was a lecture using an auxiliary application in the form of a power point which was displayed on an electronic media in the form of a laptop along with 18 people present at the column 18 GMIM Kasih Christ service and column 13 GMIM Sion Winangun service. The initial knowledge of the community from the results of the pre-test there were 13 people whose results were in the good category but after the counseling was carried out there was an increase in the good category to 17 people. It is hoped that after this counseling will increase the knowledge of the surrounding community about the dangers of disposing of waste (bathing/washing) into sewers and can take various methods or actions that can prevent various adverse effects that can arise.